Building 21-Century Indonesian Teachers’ Teaching Capacities through the Integration of Technology into Classrooms - Dan Ginting (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2018)
This research aimed to present an empirical sketch on the implementation of the IMOOC (Indonesian Massive Open Online Course). This online program sought to raise teachers’ awareness of the importance of technology for teaching while at the same time promoting their teaching skills in using technology for learning. The samples of this study included thirty-seven pre and in-service English teachers. This study found the IMOOC served as a reliable online instruction promoting essential aspects of 21-century education such as critical thinking, collaborative, creative and innovative learning, self-reliance, and individualized learning.